Flight performance of great cormorants Phalacrocorax carbo sinensis suggests sufficient muscle capacity for adaptive speed adjustment - Hedenström, Anders; Kleinheerenbrink, Marco; Åkesson, Susanne ; 0000-0001-9039-2180 (The Journal of experimental biology, 2025)
Power required to fly for a bird generally follows a U-shaped function of airspeed, with higher cost at both low and high speeds. Since power required increases with body mass faster than power available from flight muscles, larger birds may experience restricted flight speed ranges and climbing capabilities. Previous studies found limited flight performance in cormorants. Adapted for both flight and sub-surface swimming, they trade off larger flight muscles for powerful leg muscles used for diving. Our study tested if the flight performance of greater cormorants is constrained by measuring airspeed under various seasonal and wind conditions. If flight muscles severely limit the range of flight speeds, cormorants would not be able to adopt ecologically relevant speeds between seasons and not increase speed in headwinds to minimize cost of transport. Results suggest that cormorants can achieve airspeeds beyond minimum power speed, selecting speeds near maximum range during autumn migration and exceeding this range on spring migration and during foraging flights. However, expected speed adjustments to headwinds were inconsistent, with some situations lacking the anticipated responses. The cormorants demonstrated partial wind drift compensation by adjusting flight headings along coastlines, though airspeed adjustments were not always observed. While greater cormorants appear capable of reaching ecologically relevant speeds in many contexts, the overall scope of their flight speeds remains relatively narrow compared to smaller bird species. These findings indicate greater cormorants have muscle power for adaptive behaviour in some cases despite the influence of physiological constraints on their flight performance.
© 2025. Published by The Company of Biologists.